Distinct Type I Interferon Subtypes Differentially Stimulate T Cell Responses in HIV-1-Infected Individuals - Karakoese, Zehra; Schwerdtfeger, Mara; Karsten, Christina B.; Esser, Stefan; Dittmer, Ulf; Sutter, Kathrin (Frontiers in Immunology, 2022)
The expression of type I interferons (IFNs) is one of the immediate host responses during most viral infections. The type I IFN family consists of numerous highly conserved IFNα subtypes, IFNβ, and some others. Although these IFNα subtypes were initially believed to act interchangeably, their discrete biological properties are nowadays widely accepted. Subtype-specific antiviral, immunomodulatory, and anti-proliferative activities were reported and explained by differences in receptor affinity, downstream signaling events, and individual IFN-stimulated gene expression patterns. Type I IFNs and increased IFN signatures potentially linked to hyperimmune activation of T cells are critically discussed for chronic HIV infection. Here, we aimed to analyze the broad immunological effects of specific type I IFN subtypes on T and NK cell subsets during HIV-1 infection in vitro and ex vivo. Stimulation with IFNα14 and IFNβ significantly increased frequencies of degranulating (CD107a+) gut-derived CD4+ T cells and blood-derived T and NK cells. However, frequencies of IFNγ-expressing T cells were strongly reduced after stimulation with IFNα14 and IFNβ. Phosphorylation of downstream molecules was not only IFN subtype-specific; also, significant differences in STAT5 phosphorylation were exclusively observed in both healthy PBMCs and PBMCs of HIV-infected individuals, but not in healthy LPMCs assuming cell and tissue specific discrepancies. In conclusion, we observed distinct IFN subtype-specific potencies in stimulating T and NK cell responses during HIV-1-infection.